Positive leader characteristics from high-speed video observations - Saba, Marcelo M. F.; Cummins, Kenneth L.; Warner, Tom A.; Krider, E. Philip; Campos, Leandro Z. S. [UNESP]; Ballarotti, Mauricio G.; Pinto, Osmar; Fleenor, Stacy A. (Amer Geophysical Union, 2008)
Based on analyses of high-speed video recordings of cloud-to-ground lightning in Brazil and the USA, the characteristics of positive cloud-to-ground (+CG) leaders are presented. The high frame rates permitted the average, 2-dimensional speeds of development along the paths of the channels to be resolved with good accuracy. The values range from 0.3 to 6.0 x 10(5) ms(-1) with a mean of 2.7 x 10(5) ms(-1). Contrary to what is usually assumed, downward +CG leader speeds are similar to downward -CG leader speeds. Our observations also show that the speeds tend to increase by a factor of 1.1 to 6.5 as they approach the ground. The presence of short duration, recoil leaders (RLs) during the development of positive leaders reveal a highly branched structure that is not usually recorded when using conventional photographic and video cameras. The existence of the RLs may help to explain observations of UHF-VHF radiation during the development of +CG flashes.